Psychological and social consequences of non-invasive prenatal testing (NIPT): a scoping review - Valérie Labonté; Dima Alsaid; Britta Lang; Joerg J. Meerpohl (BMC, 2019)
Abstract Background Genomics-based noninvasive prenatal tests (NIPT) allow screening for chromosomal anomalies such as Down syndrome (trisomy 21). The technique uses cell-free fetal DNA (cffDNA) that circulates in the maternal blood and is detectable from 5 weeks of gestation onwards. Parents who choose to undergo this relatively new test (introduced in 2011) might be aware of its positive features (i.e. clinical safety and ease of use); however, they might be less aware of the required decisions and accompanying internal conflicts following a potential positive test result. To show the evidence on psychological and social consequences of the use of NIPT, we conducted a scoping review. Methods We systematically searched four electronic databases (MEDLINE (Ovid), Cochrane Library (Wiley), CINAHL (EBSCO) and PsychINFO (EBSCO)) for studies that investigated the psychological or social consequences of the use of NIPT by pregnant women or expecting parents. The search was limited to studies published between 2011 and August 8, 2018. We identified 2488 studies and, after removal of duplicates, screened 2007 titles and abstracts, and then assessed 99 articles in full text (both screenings were done independently in duplicate). We included 7 studies in our analysis. Results Five studies assessed anxiety, psychological distress and/or decisional regret among women with validated psychological tests like the Spielberger State Trait-Anxiety Inventory (STAI), the Pregnancy-Related Anxiety Questionnaire-Revised (PRAQ-R), the Kessler Psychological Distress Scale (K6) or the Decisional Regret Scale (DRS). Two studies assessed women's experiences with and feelings after NIPT in interviews or focus groups. The included studies were heterogeneous in location, study setting, inclusion criteria, outcome assessment, and other characteristics. Conclusions Only few studies on psychological consequences of NIPT have been identified. The studies assessed only short-term psychological consequences of NIPT at baseline and/or after receiving the results or after giving birth. Studies show that short term anxiety decreased when women received negative NIPT results and that decisional regret was generally low. We could not identify studies on long term consequences of NIPT, as well as studies on women's partners' short and long term outcomes, nor on social consequences of NIPT.